Executive functions in Chinese kindergarten children with early reading problems. (18th May 2022) - Fong, Cathy Yui‐Chi; Ho, Connie Suk‐Han
Abstract : Learning to read Chinese is a complex task that draws on a range of executive function (EF) skills since early development. However, no studies have examined EF as a potential contributing factor to early reading problems among Chinese children. The present longitudinal study identified 48 poor readers and 48 normal readers among a sample of 190 Chinese children at the end of kindergarten. Measures of EF skills (working memory, inhibition control, and cognitive flexibility) and reading outcomes (word reading, sentence reading fluency, and sentence reading comprehension) were administered to the children. The two groups were retrospectively compared on the EF measures after age and nonverbal IQ were considered. Poor readers were found to perform significantly worse than normal readers in all the examined EF skills. Correlation and regression results revealed a relatively different nature of the relationship between EF and reading in poor readers as compared with normal readers. Inhibition control predicted reading outcomes in poor readers only, while cognitive flexibility predicted reading outcomes in normal readers only. Working memory was significantly correlated to word reading in poor readers and to reading comprehension in normal readers. The results are discussed in terms of the special characteristics of the Chinese language.